Cancer Incidence Among Children in New Caledonia, 1994 to 2012. Issue 7 (October 2018) - Hartmann, Erika; Missotte, Isabelle; Dalla-Pozza, Luciano
Abstract : New Caledonia (NC) is a small French territory in the Pacific Ocean with a relatively young (32% under 20) and multiethnic population. It is divided into 3 districts: Loyalty Island, the North, and the South, each with specific population characteristics. The aim of this study was to describe childhood cancer age-standardized incidence rate (ASR) in NC, compare it with the estimated one in France, and to determine whether residence and ethnicity may have an influence on intrapopulation ASR. All incident cancer cases diagnosed between 1994 and 2012 in children (0 to 14 y) resident in NC for more than 6 months were included. With 162 registered cases, the ASR for all cancers combined was 142.2 (range, 104.9 to 193.3) cases per million children per year and was not different from what was estimated in France (156.6). However, incidence varies according to the place of residence, with a higher ASR in the Loyalty Island district for several types of neoplasms, but not according to the ethnicity. The small migratory flux between this district and the rest of the territory may have led to these results, but, because of the small number of cases, no conclusion can be drawn.